Far Wing Asymmetry of Rotational Raman Lines in Hydrogen. (2nd September 2009) - Gustafsson, Magnus
Abstract : Depolarized Raman spectra of compressed hydrogen gas have been computed rigorously previously for 36 K and 50 K (Gustafsson et al. (2009)). The far wings of the rotational lines show asymmetry that goes beyond that expected from the theory for intracollisional interference and Fano line shapes. Here we analyze theS 0 (0) line for pure hydrogen at 36 K in detail. The added asymmetry stems partly from a shape resonance which adds significant intensity to the higher frequency side of the line profile. The influence of the threshold energy for the rotational transition accounts for the remainder.